Elucidating the lignocellulose digestion mechanism coptotermes curvignathus based on carbohydrate-active enzymes profile using the meta-transcriptomic approach - Pik, Kheng Hoe; Jie, Hung King; Kian, Huat Ong; Choon, Fah Bong; Nor Muhammad Mahadi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Termites are efficient lignocellulose decomposers that thrive on woody materials and contribute to carbon mineralization in both tropical and subtropical regions. Due to hydrolytic stability and crosslinking between the polysaccharides (cellulose & hemicellulose) and the lignin via ester and ether linkages, termites would require a large variety of enzymes to degrade lignocellulose. Coptotermes curvignathus, an endemic species of termite from Southeast Asia, has been classified as an urban pest in the region and is known as the largest and most aggressive among the oriental Coptotermes spp. Its Carbohydrate-Active enzymes (CAZymes) are the main interest of this study. RNA of C. curvignathus was extracted and sequenced using Illumina Hiseq 2000 sequencing platform, and de novo assembled with Trinity pipeline. There were 101 CAZymes families in C. curvignathus digestome. CAZymes break down complex carbohydrates and glycoconjugates for a large body of biological roles and perform their function, usually with high specificity. Enzymes coding for glycosyl hydrolase (GH) families had the highest transcript abundance, accounting for about 93% of the total CAZymes reads. This was followed by CBM (≈1%), GT family (≈4%), CE family (<1 %) AA family (<2 %) and PL family (<1 %). Due to the carbohydrate diversity exceeding the number of protein folds, CAZymes have evolved from a limited number of progenitors by acquiring novel specificities at substrate and product levels. Such a dizzying array of substrates and enzymes makes C. curvignathus a high-performance lignocellulose degrader